Perencanaan Pondok Tahfidz Universitas Muhammadiyah Kendari dengan Pendekatan Arsitektur Modern - Fadel Muhammad; Annas Ma'ruf; Yudhi Dwi Hartono (Arsitektur Universitas Muhammadiyah Kendari, 2022)
As a Muslim, seeking knowledge is an obligation, moreover studying Islam. One of the places to study religion is Islamic School which focuses on memorizing and implementing Quran, in Indonesia is popularly called “Pondok Tahfidz”. The purpose of this research is to organize the building configuration and design form of Pondok Tahfidz Muhammadiyah Kendari University and apply the concept of modern architecture. This study uses a descriptive method, namely by describing the problem and situation, then analyzed quantitative and qualitative factors systematically according to the discipline of architecture to obtain the appropriate solution. The results of this study indicate that in arranging the building mass and design form, there are several things that must be considered, namely, site processing, identifying space requirements, relationships between spaces, and the amount of space for building users, as well as the basic form of building functions. So that the success in managing the mass of the building is more optimal. A Modern Architecture approach can be done by adhering to the